Histórias em quadrinhos como recurso didático para aulas de ciências do 9º ano do ensino fundamental - Camêlo, Andressa Maria Tavares (2023)
This paper proposes the use of comic books in the teaching of Science, with focus on the “Matter and energy” thematic unit. Research was performed in a 9th grade class at the José Batista de Oliveira School of Children's Education and Fundamental Teaching, located at the city of Pacatuba/CE. The comic book was elaborated and produced with the graphic design tool Canva and the subject approached in the book was “Ideas about matter and Atomic Models.” The research had the goal of analyzing the potentiality of this didactic resource in the teaching of Science, and to reach this goal, a quali-quantitative method was employed, in which it was taken into account the analysis of phenomena and of the research participants, as well as the treatment of the acquired data. A survey was applied before and after the use of the didactic resource. The survey took into account socioeconomic matters, educational matters, knowledge about the subject approached in the comic book, and the acceptance of the comic book as a didactic resource. The data were analyzed based on Discourse Analysis and the results obtained have shown that comic books can be used as a potentializing instrument in the teaching of Science. A tutorial for the crafting of comic books with the Canva platform was created as an educational project, so that it can be available for teachers who wish to create their own comic books.